Disruption of Drought Teleconnections Between ENSO‐Influenced Regions Around 1700 CE - Max C. A. Torbenson; David W. Stahle; Edward R. Cook; Benjamin I. Cook; Ulf Büntgen; Feng Chen; Ernesto Tejedor; James H. Stagge; Miroslav Trnka; Dorian J. Burnette; Weipeng Yue; Jan Esper (Geophysical Research Letters, 2025)
Abstract Our understanding of pre‐modern El Niño Southern Oscillation (ENSO) variability is reliant on proxy records, often distant from the center of ENSO activity in the equatorial Pacific Ocean. Here, we assess the relationship between reconstructed soil moisture in four distant ENSO‐influenced regions over the past 400 years. A major breakdown in the teleconnection of regional drought conditions in Asia, Eastern Australia, and North America is identified around 1700 CE. The statistically significant decline in inter‐series correlations (p < 0.01) represents a previously unknown aspect of global hydroclimate dynamics. We hypothesize that the disruption was driven by ENSO weakening and/or by a large‐scale multi‐decadal reconfiguration of ocean‐atmosphere circulation. Data assimilation estimates of soil moisture from the same regions fail to produce results of the same magnitude, potentially due to an overreliance of ENSO influence on the boundaries of spatial covariance in the underlying climate models.